Bertolt Brecht's Furcht und elend des dritten reiches : a German exile drama in the struggle against fascism - White, John J., 1940-2015 (Studies in German literature, linguistics, and culture., 2010)
Brecht's 'Furcht und Elend des Dritten Reiches' (Fear and Misery of the Third Reich) gives a compelling documentary picture of life in Nazi Germany. Close readings of individual scenes are accompanied by a detailed analysis of their role within the play's overall structure. Contrary to the assumption that it is a work of Aristotelian realism, Brecht is shown to employ covert alienation devices that are an integral part of his literary campaign against Third Reich Germany. This first study in English on the subject of Brecht and fascism offers a corrective to the overconcentration on the play's artistic aspects. It considers Brecht's relationship to the Popular Front's campaign against the National Socialist regime. Attention is paid to the play's genesis, and, in the case of 'The Private Life of the Master Race,' to the partial shift from the Third Reich of 1933-38 to the war period predicted in the original 'Furcht und Elend' cycle. The play's central theme of resistance, its propaganda value, and its political and artistic reception are addressed within their historical and ideological framework. The result is a challenging assessment of the play's strengths and limitations as a response to German totalitarianism. John J. White is Emeritus Professor of German and Comparative Literature at King's College London, and Ann White is Senior Lecturer in German at Royal Holloway, University of London.